Penataan Data Inovasi Daerah di Provinsi Jawa Timur dan Provinsi DI. Yogyakarta - Ray Septianis Kartika; Arzad Sectio (Research and Development Agency Ministry of Home Affairs, 2018)
Regional innovation data includes the development of regional innovations. The spirit of the Ministry of Home Affairs BPP after Law No.38 of 2017 was faced with problems, namely (1) regional innovation data was still in each OPD, (2) existing regional innovation data was ambiguous and not categorized according to the mandate contained in PP No .38 in 2017. The aim is to analyze the conditions and identify the process of collecting, structuring and mapping data on regional innovations. This study uses descriptive methods with loci in DIY Province and East Java Province using interviews, observation techniques, and literature searches through internet sites. Data processing and analysis methods using qualitative data analysis techniques. The results of the study identified DIY provinces as many as 57 regional innovations and 41 provinces in East Java. Data processing, structuring and mapping methods are carried out by data administrators through manual inputting and utilization of information systems. The study findings are as follows (1) the innovation data is still manual and compiled based on the participation participation in the competition, (2) Does not have a standard systematics in making databases, and (3) Weak public transparency in accessing innovation data. The study suggestion is the need to collect, organize and map regional innovation data nationally through survey research, make the Minister of Home Affairs SE related to filling in the data base format for innovation, commitments from echelon 1 and II officials in supporting regional innovation data collection efforts, conducting meetings and communication with the Ministry or Institutions involved in developing innovation in the region, and expanding networks with donor agencies in developing survey research missions. Thus the data arrangement that has been carried out comprehensively can be carried out continuously, continuously and planned.